Design and Implementation of Matryoshka-type Neutron Spectrometer. Issue 2 (February 2021) - Lv, Ning; Lv, Jinxu; Sun, Mingyan; Lv, Wenhui; Xiao, Qizhan
Abstract : Abstract: Aiming at portability and mobility, the design and implementation of a portable neutron spectrometer, namely the Matryoshka-type Neutron Spectrometer, was completed while considering the idea of a Bonner Sphere Spectrometer. The Matryoshka-type Neutron Spectrometer used a spherical 3 He proportional counter as a thermal neutron detector. A number of cylindrical acrylic cups with diameters from 4 cm to 40 cm were made as containers for water as a moderator. The Monte Carlo method was adopted in order to obtain the energy response matrix of the Matryoshka-type Neutron Spectrometer. During the measurement, each acrylic cup contained water as a moderator, and the 3 He proportional counter was set to the geometric center to perform neutron counting. With the energy response matrix obtained above, the neutron spectrum was resolved by a classical inversion algorithm. After the measurement, water was drained and the acrylic cups were placed one inside the other, like a Matryoshka doll. The design of a Matryoshka-type Neutron Spectrometer has reduced the mass and volume of the Bonner Sphere Spectrometer and was not difficult to carry around. Comparison tests acquiring background and Am-Be source neutron spectra between the Matryoshka-type Neutron Spectrometer and Bonner Sphere Spectrometer proved the effectiveness of the Matryoshka-type Neutron Spectrometer.